2009
DOI: 10.1007/s10551-008-9997-4
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Effects of Corporate Ethical Values on Employee Commitment and Performance: Examining the Moderating Role of Perceived Fairness

Abstract: corporate ethical values, ethics, job performance, commitment, organizational fairness,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 50 publications
1
40
0
2
Order By: Relevance
“…Several studies have also provided empirical support for the notion that a higher level of organizational ethics is associated positively with different individual outcomes, such as better job satisfaction (Jaramillo, Mulki, & Solomon, 2006;Pettijohn, Pettijohn, & Taylor, 2008;Valentine et al, 2011) and higher organizational commitment (e.g., Huhtala, Feldt, Hyvönen, & Mauno, 2013;Sharma, Borna, & Stearns, 2009;Treviño et al, 1998;Valentine, Godkin, & Lucero, 2002), which can reduce employees' turnover intentions (e.g., Jaramillo et al, 2006;Pettijohn et al, 2008;Valentine et al, 2011). Huhtala et al (2011) showed that ethical culture was associated with less ethical strain, less emotional exhaustion (the core dimension of burnout), and higher work engagement at the individual level.…”
Section: Ethical Culture As a Context For Well-beingmentioning
confidence: 98%
“…Several studies have also provided empirical support for the notion that a higher level of organizational ethics is associated positively with different individual outcomes, such as better job satisfaction (Jaramillo, Mulki, & Solomon, 2006;Pettijohn, Pettijohn, & Taylor, 2008;Valentine et al, 2011) and higher organizational commitment (e.g., Huhtala, Feldt, Hyvönen, & Mauno, 2013;Sharma, Borna, & Stearns, 2009;Treviño et al, 1998;Valentine, Godkin, & Lucero, 2002), which can reduce employees' turnover intentions (e.g., Jaramillo et al, 2006;Pettijohn et al, 2008;Valentine et al, 2011). Huhtala et al (2011) showed that ethical culture was associated with less ethical strain, less emotional exhaustion (the core dimension of burnout), and higher work engagement at the individual level.…”
Section: Ethical Culture As a Context For Well-beingmentioning
confidence: 98%
“…Job performance is a work-related outcome that refers to the attainment of organizational objectives measured by evaluating performance on job-related tasks (Sharma, Borna, & Stearns, 2009). Prior research has focused on the relationship between ethical climate and turnover intentions (Jaramillo, Mulki, & Solomon., 2006;Mulki, Jaramillo, & Locander, 2006).…”
Section: Caring Climatementioning
confidence: 99%
“…The effect of works ethics on organizational commitment can be moderated by fair or unfair treatment of employees which may cause satisfaction or dissatisfaction among them (Sharma, Borna & Stearns, 2009). The satisfaction level of human beings towards fairness can be explained by the Equity theory (Locke, cited in Robbins, 2003).…”
Section: Relationship Between Work Ethics and Job Satisfactionmentioning
confidence: 99%
“…In addition, Islamic work ethics do not have any influence on employees' loyalty to organizations in Turkey (Uygur, 2009). A study by Sharma et al (2009), among 204 furniture retailers in the USA, reported that fairness is important to create organizational commitment among employees.…”
Section: Relationship Between Work Ethics and Organizational Commitmentmentioning
confidence: 99%